Unraveling the resistive switching effect in ZnO/0.5Ba(Zr0.2Ti0.8)O3-0.5(Ba0.7Ca0.3)TiO3 heterostructures - Silva, J. P. B. (2017)
This work reports the effect of partial oxygen pressure, used in the deposition of the ZnO layer, on the band alignment at ZnO − 0.5Ba(Zr0.2Ti0.8)O3-0.5(Ba0.7Ca0.3)TiO3 (0.5BZT-0.5BCT) interface and on the resistive switching (RS) behavior of pulsed laser deposited ZnO/0.5BZT-0.5BCT heterostructures. X-ray photoelectron spectroscopy (XPS) has been employed to measure the valence band offset and the conduction band offset of the ZnO/0.5BZT-0.5BCT heterojunctions. The valence and conduction band offsets of the ZnO/0.5BZT-0.5BCT heterostucture with ZnO deposited at 10−2 mbar of partial oxygen pressure were found to be 0.27 and 0.80 eV, respectively. The RS effect in heterostructures is explained on the base of the charge coupling between the switchable polarization of ferroelectric layer and the non-switchable polarization of semiconductor layer. The heterostructure with ZnO deposited at 10−2 mbar of partial oxygen pressure displays optimum RS characteristics, with a switching ratio ≥ 104 and excellent retention and endurance characteristics. The optimum RS characteristics are attributed to a good interface quality with enough carrier concentration in ZnO, as evidenced by XPS.